Use of remote sensing and GIS for improved natural resources management: case study from different agroecological zones of West Africa - Junge, B.; Alabi, T.; Sonder, Kai; Marcus, S.; Abaidoo, Robert C.; Chikoye, David; Stahr, Karl (Informa UK Limited, 2010)
Historical and recent aerial photograph and satellite images were analysed to study the change of land use/land cover and soil degradation in different agroecological zones of Nigeria and Benin. The sites were characterized by an expansion of farmland at the expense of forest and shrub, fallow and uncultivated land, at an increasing rate due to population growth, food demand and land scarcity. Sheet and gully erosion were the consequences of the land use intensification and have destroyed extensive areas of farmland and grazing land. Reduced agricultural and livestock production, declining revenue, as well as increased conflict from resource competition between farmers and pastoralists are expected for the future. To combat these problems, improved land use management through continuing land inventory, generating an environmental database, developing land use plans and controlling erosion through adequate soil conservation measures are recommended.